460mpa grade h-shaped steel for building structure and method for producing the same
Patent Information
- Application Number
- CN202410236392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-01
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-01
AI Technical Summary
但该方法Nb、Cr、Ni、Cu、V合金元素含量较高,生产成本大大增加
[0042]本发明基于高强热轧H型钢的生产实际,利用高碳中锰高钒成分体系,结合开坯轧制+万能精轧+轧后控冷工艺,通过细晶强化和第二相粒子析出强化,实现轧制过程中热轧H型钢表层和芯部的不同组织转变,获得双相组织层的热轧H型钢产品,其中表层组织为铁素体+贝氏体,芯部组织为铁素体+贝氏体+珠光体。其中,芯部组织中铁素体组织面积占比不低于50%,珠光体占比在5%-10%范围,铁素体晶粒度等级在9.5级以上。产品达到的屈服强度不低于460MPa、抗拉强度580MPa~720MPa,断后伸长率不低于20%,-20℃纵向冲击功值不低于120J,且定尺长度每米平直度偏差不超过1mm,翼缘斜度偏差不超过6.5mm,满足建筑结构等行业对超大超厚规格H型钢钢桩应用需求。
Smart Images

Figure CN117966028B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal material production technology, and relates to a 460MPa grade H-beam for building structures and its production method. Background Technology
[0002] With rapid economic development, my country's infrastructure construction has also made significant progress. Especially in the last decade, my country has witnessed a surge in the development of high-rise steel structure buildings. Steel materials, as the main structural components, support the continuous development of my country's infrastructure construction, while profiled steel products, with their simple cross-sections and high load-bearing capacity, are widely used in building structures.
[0003] Currently, commonly used structural steel profiles in the building structure field include various types such as H-beams, angle steel, and channel steel, with strength primarily at the 355MPa level. However, with the increasing vertical height of building structures, ultra-high-rise, ultra-large, and high-strength structural steel profiles are becoming the future direction of the construction market. Among these, H-beams, as the main structural steel product, have a large number of engineering applications in the current building structure market due to their green environmental protection, economic practicality, and superior performance. Considering the seismic resistance and foundation strength of high-rise buildings, the steel pile-concrete casting method is widely used for foundation construction. Since hot-rolled H-beams (steel piles) for building structures are vertically driven into the soft soil of the foundation, strict requirements are placed on the straightness and flange slope of the H-beams themselves. Furthermore, considering the thickness requirements of H-beams and the current level of production control, it is difficult to guarantee the dimensional shape of thick-gauge H-beam products. To meet the market demands of future building structures, it is essential to develop ultra-strong H-beams for building structures.
[0004] The current state of the technology is as follows:
[0005] The patent document published on September 8, 2010, with publication number CN101824581A and titled "A high-strength weathering steel plate with a yield strength of 450MPa and its production method," describes a steel composition by mass percentage as follows: C: 0.040%-0.080%, Si: 0.15%-0.35%, Mn: 1.20%-1.40%, P: ≤0.025%, S: ≤0.008%, Nb: 0.015%-0.035%, Cu: 0.25%-0.40%, Ni: 0.12%-0.35%, Cr: 0.45%-0.75%, Als: 0.020%-0.045%, with the remainder being Fe and unavoidable impurity elements. The steel produced has a yield strength ≥485MPa, tensile strength ≥590MPa, elongation ≥28%, and Charpy impact energy ≥105J at -40℃ V-notch. However, the thickness of this product is limited to below 8mm, and alloying elements such as Cr, Ni, Cu, and N are added. Furthermore, laminar cooling is required after rolling, which greatly increases production costs and energy consumption.
[0006] The patent document published on September 11, 2013, with publication number CN103290331A and titled "A high-strength, high-corrosion-resistant steel plate with a yield strength of 450 MPa and its production method," describes the steel's composition as follows: C: 0.002%-0.005%, Si: 0.15%-0.35%, Mn: 0.1%-0.9%, P: ≤0.012%, S: ≤0.008%, Cu: 0.25%-0.5%, Cr: 2.80%-4.0%, Ni: 0.12%-0.35%, Al: 0.01%-0.05%, Nb: 0.015%-0.030%, with the balance being Fe and unavoidable impurity elements. This invention produces steel with a yield strength ≥450MPa, tensile strength ≥550-750MPa, elongation ≥20%, and a relative corrosion rate less than 30% of Q345B for atmospheric corrosion resistance. However, this invention contains too many alloying elements, especially excessive Cr, requiring a special segmented laminar flow cooling process after rolling, increasing production costs and equipment energy consumption. Furthermore, the impact performance of the product is not mentioned.
[0007] The patent document CN102925798A, published on February 13, 2013, entitled "A steel with a yield strength of 450MPa for railway freight car parts and its production method," describes a steel composition of: C: 0.01%-0.07%, Si: ≤0.045%, Mn: 0.45-1.15%, P: ≤0.025%, S: ≤0.010%, Nb: 0.01%-0.08%, V: 0.02%-0.10%, N: 0.0030%-0.010%. This invention, based on C-Mn and using a matching process, refines the grains and strengthens the steel through precipitation, producing a steel with a yield strength ≥450MPa, tensile strength ≥550MPa, elongation ≥20%, and a Charpy impact energy ≥70J at -40℃ V-notch, while also exhibiting good weldability and low cost. However, the thickness of this steel is limited to less than 14mm, which does not meet the product specification requirements of current super-large building structures. Furthermore, laminar cooling is required after rolling, necessitating the investment in cooling equipment, resulting in high production costs.
[0008] Patent document CN103255353A, published on August 21, 2013, entitled "A Rolling Process for Vanadium-Containing Weather-Resistant Hot-Rolled H-Beams with a Yield Strength of 450MPa," discloses a rolling process for vanadium-containing weather-resistant hot-rolled H-beams with a yield strength of 450MPa. The vanadium-containing weather-resistant hot-rolled H-beams, by mass percentage, have the following composition: C: 0.09%-0.11%, Si: 0.4%. The alloy composition is as follows: Mn: 1.25%-1.38%, P: 0.015%-0.022%, S: 0.008%-0.014%, Cu: 0.27%-0.33%, Cr: 0.35%-0.42%, Ni: 0.25%-0.32%, V: 0.073%-0.087%, AlS: 0.010%-0.025%, with the remainder being iron and residual trace impurities. However, the addition of alloying elements such as Cr, Ni, and Cu increases the production cost, and the need for two-stage rapid cooling after rolling significantly increases energy consumption.
[0009] The patent document published on December 3, 2019, with publication number CN110527915A and titled "A 460MPa Grade Hot-Rolled H-Beam and Its Production Method," discloses a 460MPa grade hot-rolled H-beam and its production method. Its chemical composition and content by weight percentage are: C 0.08%-0.11%, Si 0.20%-0.30%, Mn 0.50%-0.70%, P≤0.015%, S≤0.010%, Cr 1.30%-1.80%, Ni 0.60%-0.90%, Cu 0.30%-0.40%, Mo 0.15%-0.25%, Nb 0.030%-0.050%, V 0.060%-0.100%, Al 0.015-0.030%, with the remainder being Fe and unavoidable impurities. The production method includes billet heating, initial rolling, first and second stage universal rolling, and air cooling. This invention, through reasonable component proportioning and process control, can obtain hot-rolled H-beams with a yield strength of 460MPa, possessing excellent toughness, Z-axis properties, fire resistance, corrosion resistance, and seismic resistance. The product of this invention incorporates alloying elements such as Cr, Ni, Cu, V, and Mo to meet the requirements of special properties such as fire resistance and corrosion resistance, significantly increasing production costs.
[0010] The patent document published on October 12, 2018, with publication number CN108642381A and titled "A hot-rolled high-toughness low-temperature resistant H-beam with a yield strength of 460MPa and its preparation method," has the following chemical composition by weight percentage: C: 0.03%-0.07%, Si≤0.3%, Mn: 1.20%-1.40%, Nb: 0.015%-0.030%, V: 0.10%-0.15%, Ti: 0.015%-0.025%, Ni: 0.25%-0.45%, Cr: 0.30%-0.50%, Als: 0.01%-0.06%, N: 0.010%-0.023%, P≤0.015%, S≤0.010%, O≤0.004%, with the remainder being Fe and unavoidable impurities. This invention employs a nitrogen-containing composite microalloying design, achieving a strength of over 460 MPa while maintaining high toughness on a conventional hot-rolled H-beam mill. However, this invention involves the addition of alloying elements such as Cr, Ni, Ti, V, and Nb, and requires strict control over the nitrogen content in the steel grade. This results in a complex production process and significantly increased production costs.
[0011] Patent document CN108754327A, published on November 6, 2018, entitled "A High-Toughness Weather-Resistant Hot-Rolled H-Beam for Bridge Structures with a Yield Strength of 460MPa and its Production Method," discloses a high-toughness weather-resistant hot-rolled H-beam for bridge structures with a yield strength of 460MPa and its production method. The hot-rolled H-beam comprises the following chemical composition by weight percentage: C: 0.08%-0.11%, Si: The alloy composition is as follows: Mn: 1.30%-1.50%, P: ≤0.020%, S: ≤0.015%, Cr: 0.50%-0.65%, Ni: 0.30%-0.40%, Cu: 0.30%-0.40%, V: 0.075%-0.095%, Nb: 0.015%-0.025%, Alt: 0.015%-0.030%, with the remainder being Fe and trace residual elements. Through reasonable component ratios, reduction distribution, and temperature-controlled rolling, utilizing fine-grain strengthening, precipitation strengthening, and phase transformation strengthening mechanisms, mechanical properties were obtained with ReL not less than 460 MPa, Rm not less than 570 MPa, A not less than 20%, and KV2 not less than 150 J at -40℃. However, this method has high Nb, Cr, Ni, Cu, and V alloy element contents, significantly increasing production costs.
[0012] In summary, while significant technological advancements have been made in the development of 460MPa grade high-strength hot-rolled H-beams, the processes and performance of some products remain limited by production equipment and on-site conditions to meet the current application demands in the building structure sector. Therefore, it is essential to develop hot-rolled H-beam products that meet the requirements of high-strength building structures, taking into account existing production equipment and practical production realities. Summary of the Invention
[0013] The purpose of this invention is to provide a 460MPa grade H-beam for building structures and its production method. Through composition design and a reasonable rolling reduction ratio, the invention meets the shape control technology for the biphasic microstructure transformation process and straightness deviation in actual production. Combined with actual on-site production process operation, it realizes the production of high-strength hot-rolled H-beam products through a process of billet rolling + universal precision rolling + cooling control. The product has a yield strength of not less than 460MPa, a tensile strength range of 580MPa to 720MPa, an elongation after fracture of not less than 20%, a longitudinal impact energy value of not less than 120J at -20℃, and a straightness deviation of not more than 1mm per meter and a flange slope deviation of not more than 6.5mm, meeting the requirements of the domestic building structure industry for high-strength hot-rolled H-beams.
[0014] The specific technical solution of this invention is as follows:
[0015] A type of H-beam for building structures with a strength of 460 MPa, comprising the following components by weight percentage:
[0016] C: 0.16%-0.20%, Si: 0.38%-0.45%, Mn: 1.10%-1.30%, P: ≤0.025%, S: ≤0.020%, N: 0.0050%-0.020%, Nb: 0.010%-0.030%, V: 0.060%-0.090%, Alt: 0.010%-0.025%, with the remainder being Fe and trace residual elements.
[0017] The composition of the H-beams used in the 460MPa grade building structure meets the following requirements: 0.15≤Nb / V≤0.30, 0.3≤VN / VFe≤0.5; wherein the vanadium (V) element can be added by a ratio of vanadium-nitrogen alloy (VN) and vanadium-iron alloy (VFe);
[0018] The flange thickness of the 460MPa grade H-beams for building structures is 20mm-60mm, and the web thickness / flange thickness ratio is 0.5-0.8, which meets the current specifications and application range of steel products for building structures.
[0019] This invention provides a method for producing 460MPa grade H-beams for building structures, comprising the following process flow:
[0020] Hot metal pretreatment → converter smelting → argon blowing refining → LF refining → special-shaped billet casting → billet heating → billet rolling → universal precision rolling → controlled cooling → air cooling on cooling bed → length straightening → bundling.
[0021] The specific steps in the rolling stage are as follows:
[0022] The billet heating process involves heating the shaped billet in the furnace at a temperature of 1200℃-1230℃ for 90-120 minutes, including a soaking zone temperature of 30-60 minutes, to ensure the austenite grain size is not lower than grade 9.0. Simultaneously, excessive heating time is prevented, as this could lead to austenite grain growth and adversely affect the initial microstructure during subsequent rolling. The billet temperature after descaling before being sent to the billet mill is ensured to be not lower than 1130℃.
[0023] The initial rolling process involves high-pressure water descaling before the initial rolling mill. Descaling must ensure the billet surface is clean and free of residual iron oxide scale. The initial rolling temperature is 1120℃-1160℃, and the final rolling temperature is not lower than 1050℃. This ensures that the temperature before the initial rolling stage is higher than the complete recrystallization temperature of austenite, and that the entire initial rolling stage achieves a 40%-60% section compression ratio. Through the reduction action of initial rolling, the original austenite grains are refined, promoting the formation of fine austenite grain boundaries, increasing the grain boundary orientation difference of the original structure, and facilitating the subsequent transformation of austenite into ferrite and pearlite.
[0024] The universal finishing rolling process involves an initial rolling temperature not exceeding 1050℃. This process primarily ensures that the large deformation during continuous rolling achieves compression changes in the flange thickness of the irregularly shaped billet, guaranteeing that the flange thickness compression ratio throughout the finishing rolling stage is not less than 45% of the billet flange thickness, thus achieving grain refinement during the finishing rolling stage. Simultaneously, it should be ensured that within the low-temperature finishing rolling temperature range of 930℃-950℃, the overall cross-sectional compression ratio is not less than 5% of the billet cross-sectional area. This low-temperature finishing rolling temperature range facilitates the precipitation and strengthening effect of second-phase particles of vanadium alloying elements.
[0025] The controlled cooling process involves selecting different cooling parameters based on the flange thickness. By controlling water pressure, roller conveyor speed, and temperatures before and after cooling, the transformation of austenite to bainite at low temperatures is achieved. Excessive cooling intensity, which could lead to complete bainite transformation in the core and excessively high material strength, results in decreased ductility and toughness. Furthermore, by controlling cooling process parameters, deformation of the upper and lower flanges and web is ensured. Controlled cooling temperature monitoring ensures internal stress balance in the finished H-beam, preventing "inner expansion and outer widening" of the H-beam's shape due to the cooling process, which would lead to significant flatness deviations and fail to meet the actual requirements of steel piles. Therefore, by adjusting the controlled cooling process, calibrated temperature measurements are performed at a distance of B / 4 from the end of the four flanges on both sides of the H-beam (B is the web width of the H-beam) to control the temperature of the upper and lower flanges of the H-beam product. Among these parameters, T... A-OS For the operating side upper flange temperature, T A-DS For the temperature of the upper flange on the drive side, T B-OS For operating lower wing edge temperature, T B-DS The temperature of the lower flange on the drive side. To accurately control the dimensional deviations of the product, the following controls are implemented:
[0026] For flange thickness t2 where 20mm < t2 ≤ 40mm, the temperature before cooling (T) A-OS +T B-OS / 2) The temperature is controlled at 850℃-900℃, the running speed of the controlled cooling roller conveyor is 1.5-1.8m / s, and the water pressure is 1.5MPa-1.8MPa; after cooling, T A-OS T B-OS T A-DS T B-DS Temperatures were all controlled between 530℃ and 570℃, with 0 ≤ T A-OS -T B-OS ≤15 and |T A-OS -T A-DS |≤20;
[0027] For flange thickness t2 where 40mm < t2 ≤ 60mm, the temperature before cooling (T) A-OS +T B-OS / 2) The temperature is controlled at 880℃-930℃, the roller conveyor speed is 1.2-1.5m / s, the water pressure is 2.0MPa-2.2MPa, and after cooling, T A-OS T B-OS T A-DS T B-DS Temperatures were all controlled between 570℃ and 630℃, with 0 ≤ T A-OS -T B-OS ≤25 and |T A-OS -T A-DS |≤25.
[0028] The air cooling of the cooling bed: After the controlled cooling process is completed, the rolled workpiece is transported to the cooling bed by the transport roller conveyor and air-cooled to room temperature.
[0029] The fixed-length straightening process involves cutting the finished product on the cooling bed into multiple or fixed lengths, with the fixed length not exceeding 15m. The cut product is then transported to the straightening machine for straightening.
[0030] Bundling: The finished products of fixed length are bundled, packaged, and stored in the warehouse for shipment.
[0031] The design concept of this invention is as follows:
[0032] Carbon (C): Carbon is the most basic element in steel. Through its combination with other elements, it plays a significant role in improving the strength of steel. In order to meet the requirements of high strength level, and considering the high strength requirements of the product, the lower limit is set at 0.16wt%. Considering the difficulty of controlling the steelmaking process and the adverse effects on the plasticity of the material caused by excessive carbon content, the upper limit is set at 0.20wt%.
[0033] Silicon (Si): It exists in steel in solid solution form and has a strong solid solution strengthening effect, which can significantly strengthen ferrite. To obtain high strength, the lower limit is set at 0.38 wt%. However, when Si is higher than 0.45%, the toughness and plasticity of steel decrease significantly, so the upper limit is set at 0.45 wt%.
[0034] Manganese (Mn): Effectively inhibits the transformation of ferrite to pearlite, greatly improving the low-temperature toughness of the material. It can also lower the phase transformation temperature, which is beneficial for the transformation of austenite under low-temperature conditions. However, excessive manganese content can cause segregation defects inside the cast billet; therefore, the Mn content should be controlled between 1.10-1.30 wt%.
[0035] Phosphorus (P): It tends to segregate in steel, which greatly reduces the plasticity and toughness of the steel and has a certain impact on the surface quality of the steel. Considering the difficulty of removing P in the steelmaking process, the upper limit is set at 0.025 wt%.
[0036] Sulfur (S): It has a significant impact on the toughness of steel. It is easy to accumulate and segregate within and at the boundaries of grains. In particular, it readily forms MnS inclusions with manganese, making the matrix structure of the material prone to the boundary initiation of cracks. Considering the difficulty of desulfurization in the steelmaking process, the upper limit is set at 0.020 wt%.
[0037] Nitrogen (N): It can form important precipitates with microalloying elements in steel, significantly improving the strength and toughness of steel. It can also form stable vanadium nitride precipitates with vanadium, achieving important effects of grain refinement and precipitation strengthening. The lower limit is set at 0.0050 wt%. At the same time, considering the actual steelmaking level and impact, excessive nitrogen content can easily form aluminum-nitrogen inclusions, which can easily cause surface cracks in the billet and reduce the plasticity and toughness of the material. The lower limit is set at 0.020%.
[0038] Vanadium (V): Vanadium is one of the most important microalloying elements in steel, exhibiting significant grain refinement strengthening, precipitation strengthening, and sedimentation strengthening effects. Vanadium readily forms carbonitrides with nitrogen, effectively preventing excessive grain growth, promoting the transformation of austenite to ferrite, facilitating the precipitation of soft and tough phases, and improving the low-temperature toughness of the material. Furthermore, during the post-rolling cooling process, the precipitation of carbonitrides plays a certain strengthening role. For high-strength steel, considering the strengthening effect of vanadium, a lower limit of 0.060 wt% is set. However, due to limitations in the actual rolling process control, excessively high vanadium content cannot effectively precipitate VN particles, and has no significant impact on the actual mechanical properties of the steel. Moreover, excessive vanadium alloying elements lead to a dramatic increase in production costs; therefore, an upper limit of 0.090 wt% is set. Considering the cost of the alloy and the nitrogen fixation effect, vanadium is added in a VN / VFe ratio. To ensure the precipitation effect of VN compounds, the VN / VFe alloy ratio should not be less than 0.3. At the same time, to save production costs, the actual VN alloy input should not be too high. Therefore, the V content ratio should meet the requirement of 0.3≤VN / VFe≤0.5.
[0039] Niobium (Nb) is an important element in microalloying. When matched with vanadium in certain amounts, it can achieve the effects of fine grain strengthening and second-phase particle strengthening. At the same time, a small amount of niobium can achieve the effect of solid solution strengthening. The lower limit is set at 0.010 wt%. However, if the niobium content is too high, it is easy to form a brittle ferrite phase, which reduces the toughness of the material and is prone to billet cracks during continuous casting. Therefore, the upper limit is set at 0.030 wt%.
[0040] In addition, niobium and vanadium are effective microalloying elements in steel. When the two achieve the superposition strengthening effect of third phase particles, they need to meet a certain ratio. Furthermore, when the ratio of niobium and vanadium is too high, it is easy to reduce the brittle temperature range of steel, which can easily generate original cracks in the billet during the billet drawing process. During the subsequent rolling process, the crack source of the billet cannot be pressed together, resulting in cracks on the surface of the finished product. Therefore, the ratio is limited to 0.15≤Nb / V≤0.30.
[0041] Aluminum (Alt): A strong oxidizing element that can be used for deoxidation in steelmaking. In addition, aluminum can precipitate in combination with nitrogen, which can refine austenite grains; the lower limit is set at 0.010 wt%. However, excessive aluminum content significantly reduces the plasticity and toughness of the material, and it can easily cause brittle formation in continuously cast irregular billets, leading to leaks and affecting production safety; the upper limit is set at 0.025 wt%.
[0042] This invention is based on the actual production of high-strength hot-rolled H-beams. Utilizing a high-carbon, medium-manganese, and high-vanadium composition system, combined with a process of initial rolling + universal finishing rolling + post-rolling controlled cooling, it achieves different microstructure transformations in the surface and core of the hot-rolled H-beam during rolling through fine-grain strengthening and second-phase particle precipitation strengthening. This results in a hot-rolled H-beam product with a two-phase microstructure, where the surface microstructure is ferrite + bainite, and the core microstructure is ferrite + bainite + pearlite. Specifically, the ferrite microstructure accounts for no less than 50% of the core microstructure, the pearlite microstructure accounts for 5%-10%, and the ferrite grain size is grade 9.5 or higher. The product achieves a yield strength of not less than 460MPa, a tensile strength of 580MPa to 720MPa, an elongation after fracture of not less than 20%, a longitudinal impact energy of not less than 120J at -20℃, and a straightness deviation of not more than 1mm per meter of the fixed length and a flange slope deviation of not more than 6.5mm, meeting the application requirements of the building structure and other industries for ultra-large and ultra-thick H-beam steel piles. Attached Figure Description
[0043] Figure 1 The surface microstructure of H-beam steel in Example 1 is ferrite + bainite.
[0044] Figure 2 The microstructure of the H-type steel core in Example 1 is ferrite + bainite + pearlite, with ferrite accounting for 55% of the area, pearlite accounting for 8%, and the ferrite grain size grade being 9.5.
[0045] Figure 3 Electron micrograph of the core tissue in Example 1;
[0046] Figure 4 This refers to the temperature control point for the controlled cooling process of H-beams. Detailed Implementation
[0047] The following description of implementation examples, combined with metallographic images, provides a more detailed explanation of the specific embodiments of the present invention.
[0048] Examples 1-4
[0049] A type of H-beam for building structures with a strength of 460MPa has the composition shown in Table 1. The balance not shown in Table 1 is Fe and unavoidable impurities.
[0050] Comparative Examples 1-4
[0051] A type of H-beam for building structures with a strength of 460MPa has the composition shown in Table 1. The balance not shown in Table 1 is Fe and unavoidable impurities.
[0052] Table 1. Chemical composition of the examples and comparative examples (unit: wt%)
[0053]
[0054]
[0055] The production methods for 460MPa grade H-beams used in building structures in each embodiment and comparative example include the following process flow:
[0056] Hot metal pretreatment → converter smelting → argon blowing refining → LF refining → special-shaped billet casting → billet heating → billet rolling → universal precision rolling → controlled cooling → air cooling on cooling bed → length straightening → bundling.
[0057] The specific steps in the rolling stage are as follows:
[0058] The billet heating process involves heating the shaped billet in the furnace at a temperature of 1200℃-1230℃ for 90-120 minutes, including a soaking zone temperature of 30-60 minutes, to ensure the austenite grain size is not lower than grade 9.0. Simultaneously, excessive heating time is prevented, as this could lead to austenite grain growth and adversely affect the initial microstructure during subsequent rolling. The billet temperature after descaling before being sent to the billet mill is ensured to be not lower than 1130℃.
[0059] The initial rolling process involves high-pressure water descaling before the initial rolling mill. Descaling must ensure the billet surface is clean and free of residual iron oxide scale. The initial rolling temperature is 1120℃-1160℃, and the final rolling temperature is not lower than 1050℃. This ensures that the temperature before the initial rolling stage is higher than the complete recrystallization temperature of austenite, and that the entire initial rolling stage achieves a 40%-60% section compression ratio. Through the reduction action of initial rolling, the original austenite grains are refined, promoting the formation of fine austenite grain boundaries, increasing the grain boundary orientation difference of the original structure, and facilitating the subsequent transformation of austenite into ferrite and pearlite.
[0060] The universal finishing rolling process involves an initial rolling temperature not exceeding 1050℃. This process primarily ensures that the large deformation during continuous rolling achieves compression changes in the flange thickness of the irregularly shaped billet, guaranteeing that the flange thickness compression ratio throughout the finishing rolling stage is not less than 45% of the billet flange thickness, thus achieving grain refinement during the finishing rolling stage. Simultaneously, it should be ensured that within the low-temperature finishing rolling temperature range of 930℃-950℃, the overall cross-sectional compression ratio is not less than 5% of the billet cross-sectional area. This low-temperature finishing rolling temperature range facilitates the precipitation and strengthening effect of second-phase particles of vanadium alloying elements.
[0061] The controlled cooling process involves selecting different cooling parameters based on the flange thickness. By controlling water pressure, roller conveyor speed, and temperatures before and after cooling, the transformation of austenite grains to bainite at low temperatures is achieved. Excessive cooling intensity, however, prevents complete bainite transformation in the core, leading to excessively high material strength and decreased ductility and toughness. Furthermore, controlling cooling process parameters ensures proper cooling deformation of the upper and lower flanges and web. Controlled cooling temperature monitoring ensures internal stress balance in the finished H-beam, preventing "inner expansion and outer widening" of the H-beam's shape due to the cooling process, which would result in significant flatness deviations and fail to meet the actual requirements of steel piles. Therefore, by adjusting the controlled cooling process and calibrating the temperature at the outer edge of the four flanges at point B / 4 from the end, the temperature of the upper and lower flanges of the H-beam is controlled. Specifically, T... A-OS For the operating side upper flange temperature, T A-DS For the temperature of the upper flange on the drive side, T B-OS For operating lower wing edge temperature, T B-DS Temperature of the lower flange on the drive side, in °C. To accurately control dimensional deviations of the product, the following controls are implemented:
[0062] For flange thickness t2 where 20 < t2 ≤ 40, the temperature before cooling (T) A-OS +T B-OS / 2) The temperature is controlled at 850℃-900℃, the running speed of the controlled cooling roller conveyor is 1.5-1.8m / s, and the water pressure is 1.5MPa-1.8MPa; after cooling, T A-OS T B-OS T A-DS T B-DS Temperatures were all controlled between 530℃ and 570℃, with 0 ≤ T A-OS -T B-OS ≤15 and |T A-OS -T A-DS |≤20;
[0063] For flange thickness t2 where 40 < t2 ≤ 60, the temperature before cooling (T) A-OS +T B-OS / 2) The temperature is controlled at 880℃-930℃, the roller conveyor speed is 1.2m / s-1.5m / s, the water pressure is 2.0MPa-2.2MPa, and after cooling T A-OS T B-OS T A-DS T B-DS Temperature controlled between 570℃ and 630℃, 0 ≤ T A-OS -T B-OS ≤25 and |T A-OS -T A-DS |≤25.
[0064] The air cooling of the cooling bed: After the controlled cooling process is completed, the rolled workpiece is transported to the cooling bed by the transport roller conveyor and air-cooled to room temperature.
[0065] The fixed-length straightening process involves cutting the finished product on the cooling bed into multiple or fixed lengths, with the fixed length not exceeding 15m. The cut product is then transported to the straightening machine for straightening.
[0066] Each embodiment and comparative example was produced according to the above method, and the specific process parameters are shown in Tables 2 and 3.
[0067] Table 2. Main process parameters for each embodiment and comparative example.
[0068]
[0069] Note: The meanings of the symbols in Table 2 are as follows:
[0070] ΔS1—Difference in rolling cross-sectional area during the initial rolling stage
[0071] S—Cross-sectional area of the billet
[0072] Δt2—Flange thickness variation during finishing rolling stage
[0073] T2—Burn flange thickness
[0074] ΔS t —Difference in cross-sectional area change during finishing rolling within the temperature range of 930℃~950℃
[0075] Table 3 shows the measured outlet temperatures ( / °C) of the controlled cooling process in each embodiment and comparative example.
[0076]
[0077]
[0078] The product mix and properties of the H-beams produced in each embodiment and comparative example are shown in Tables 4 and 5.
[0079] Table 4. Product microstructure of H-beams produced in each embodiment and comparative example.
[0080]
[0081] Table 5. Product performance of H-beams produced in each embodiment and comparative example.
[0082]
[0083] As shown in Tables 1-5, the H-beams produced using the method described in this invention have a yield strength of 471MPa-528MPa, a tensile strength of 599MPa-625MPa, an elongation of 20.5%-23.0%, a longitudinal impact energy of 124J-143J at -20℃, a straightness deviation per meter of fixed length of 0.46mm-0.82mm, and a flange slope deviation of 3.5mm-6.1mm. This indicates that the products have good strength and toughness, and the product dimensions and shape are precisely controlled, meeting the requirements for H-beams in the field of building structural engineering.
[0084] In Tables 1-4, the data underlined horizontally represents data that does not meet the requirements of this invention. Based on the comparative examples and embodiments, we can conclude that:
[0085] Comparative Example 1 does not meet the requirement of 0.3≤VN / VFe≤0.5. Comparative Example 1 uses a ratio of VN / VFe=0.2, and the product strength does not meet the requirement of 460MPa.
[0086] Comparative Example 2 does not meet the requirement of 0.15≤Nb / V≤0.30. Comparative Example 2 uses a ratio of Nb / V=0.35. Although the strength of the product meets the strength requirement, cracks appear on the surface of the product.
[0087] Comparative Examples 3 and 4 do not meet the requirements for flange thickness of 40-60mm, roller conveyor speed of 1.2-1.5m / s, and water pressure of 2.0MPa-2.2MPa. Comparative Example 3 uses a water pressure of 1.8MPa, which is insufficient for cooling. The core structure of the product is ferrite + pearlite, resulting in a strength of less than 460MPa and poor plasticity. Comparative Example 4 uses a roller conveyor speed of 1.0m / s, which is excessive for cooling. The core structure of the product is ferrite + bainite + pearlite, resulting in high strength and a tensile strength of 725MPa, exceeding the standard requirements. At the same time, the flange slope of the products in Comparative Examples 3 and 4 is too large, which does not meet the standard requirements.
Claims
1. A type of H-beam for building structures with a strength of 460MPa, characterized in that, The 460MPa grade H-beams for building structures comprise the following composition by weight percentage: C: 0.16%-0.20%, Si: 0.38%-0.45%, Mn: 1.10%-1.30%, P: ≤0.025%, S: ≤0.020%, N: 0.0050%-0.020%, Nb: 0.010%-0.030%, V: 0.060%-0.090%, Alt: 0.010%-0.025%, with the remainder being Fe and trace residual elements; Vanadium is added in a ratio of 0.3 ≤ VN / VFe ≤ 0.5; The composition of the H-beams used in the 460MPa grade building structure meets the following requirements: 0.15≤Nb / V≤0.30; The flange thickness of the H-beams used in the 460MPa grade building structure is 20mm-60mm, and the web thickness / flange thickness ratio is 0.5-0.
8. The surface microstructure of the 460MPa grade H-beams for building structures is ferrite + bainite, and the core microstructure is ferrite + bainite + pearlite; wherein, the ferrite microstructure area accounts for not less than 50% of the core microstructure, the pearlite microstructure accounts for 5%-10% of the core microstructure, and the ferrite grain size grade is above 9.
5. The longitudinal impact energy value of the 460MPa grade H-beams used in building structures at -20℃ shall not be less than 120J, and the straightness deviation per meter of the fixed length shall not exceed 1mm, and the flange slope deviation shall not exceed 6.5mm.
2. A method for producing 460MPa grade H-beams for building structures as described in claim 1, characterized in that, The production method includes the following process flow: Hot metal pretreatment → Converter smelting → Argon blowing refining → LF refining → Special-shaped billet casting → Billet heating → Billet rolling → Universal precision rolling → Controlled cooling → Cooling bed air cooling → Length straightening → Bundling.
3. The production method according to claim 2, characterized in that, The billet heating: the shaped billet is heated to 1200℃-1230℃ in the heating furnace for 90 min-120 min, of which the temperature of the soaking zone is 30 min-60 min.
4. The production method according to claim 2, characterized in that, The initial rolling process involves an initial rolling temperature of 1120℃-1160℃ and a final rolling temperature of not less than 1050℃, achieving a cross-sectional compression ratio of 40%-60% throughout the initial rolling stage.
5. The production method according to claim 2, characterized in that, The universal finishing mill: the initial rolling temperature does not exceed 1050℃, and the flange thickness compression ratio during the entire finishing rolling stage is not less than 45% of the billet flange thickness.
6. The production method according to claim 2 or 5, characterized in that, The universal precision rolling: within the low-temperature precision rolling temperature range of 930℃-950℃, the compression ratio of the entire cross section is not less than 5% of the billet cross section area.
7. The production method according to claim 2, characterized in that, The controlled cooling is as follows: for flange thickness t2 where 20mm < t2 ≤ 40mm, the temperature before cooling (T) is... A-OS +T B-OS / 2) The temperature is controlled at 850℃-900℃, the running speed of the controlled cooling roller conveyor is 1.5-1.8m / s, and the water pressure is 1.5MPa-1.8MPa; after cooling, T A-OS T B-OS T A-DS T B-DS Temperatures were all controlled between 530℃ and 570℃, and 0℃ ≤ T A-OS -T B-OS ≤15℃ and |T A-OS -T A-DS ≤20℃; For flange thickness t2 where 40mm < t2 ≤ 60mm, the temperature before cooling (T) A-OS +T B-OS / 2) The temperature is controlled at 880℃-930℃, the roller conveyor speed is 1.2-1.5m / s, the water pressure is 2.0MPa-2.2MPa, and after cooling T A-OS T B-OS T A-DS T B-DS Temperatures were all controlled between 570℃ and 630℃, and 0℃ ≤ T. A-OS -T B-OS ≤25℃ and |T A-OS -T A-DS ≤25℃; Among them, T A-OS For the operating side upper flange temperature, T A-DS For the temperature of the upper flange on the drive side, T B-OS For the operating side lower wing temperature, T B-DS The temperature is measured at the lower flange of the transmission side; the temperature measurement location is the calibrated temperature measurement at a distance of B / 4 from the end of the four flanges on both sides of the H-beam.
Citation Information
Patent Citations
High-yield strength (450MPa), high-strength and weather-resistant steel plate and production method thereof
CN101824581A
Steel with yield strength of 450MPa for railway wagon parts and production method
CN102925798A
Rolling process of vanadium-containing weather-resistant hot rolled H-shaped steel having yield strength of 450 MPa
CN103255353A
High-strength and high-corrosion-resistance steel plate material with yield strength of 450 MPa and production method thereof
CN103290331A
Hot-rolled high-toughness low-temperature-resistant H-shaped steel with yield strength of 460 MPa and preparation method thereof
CN108642381A